Spectroscopic decomposition of the galaxy and halo of the cD galaxy NGC 3311 - Johnston, Evelyn J.; Merrifield, Michael; Aragón-Salamanca, Alfonso (Oxford University Press, 2018)
Information on the star-formation histories of cD galaxies and their extended stellar haloes lie in their spectra. Therefore, to determine whether these structures evolved together or through a two-phase formation, we need to spectroscopically separate the light from each component. We present a pilot study to use BUDDI to fit and extract the spectra of the cD galaxy NGC 3311 and its halo in an Integral Field Spectroscopy datacube, and carry out a simple stellar populations analysis to study their star-formation histories. Using MUSE data, we were able to isolate the light of the galaxy and its halo throughout the datacube, giving spectra representing purely the light from each of these structures. The stellar populations analysis of the two components indicates that, in this case, the bulk of the stars in both the halo and the central galaxy are very old, but the halo is more metal poor and less α-enriched than the galaxy. This result is consistent with the halo forming through the accretion of much smaller satellite galaxies with more extended star formation. It is noteworthy that the apparent gradients in age and metallicity indicators across the galaxy are entirely consistent with the radially-varying contributions of galaxy and halo components, which individually display no gradients. The success of this study is promising for its application to a larger sample of cD galaxies that are currently being observed by IFU surveys.